2017
DOI: 10.1371/journal.pone.0177768
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific effect of CPB2 Ala147Thr but not Thr325Ile variants on the risk of venous thrombosis: A comprehensive meta-analysis

Abstract: BackgroundThrombin activatable fibrinolysis inhibitor (TAFI), encoded by the Carboxypeptidase B2 gene (CPB2), is an inhibitor of fibrinolysis and plays a role in the pathogenesis of venous thrombosis. Experimental findings support a functional role of genetic variants in CPB2, while epidemiological studies have been unable to confirm associations with risk of venous thrombosis. Sex-specific effects could underlie the observed inconsistent associations between CPB2 genetic variants and venous thrombosis.Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 64 publications
1
6
0
1
Order By: Relevance
“…Ethnic variation among TAFI haplotypes and SNPs should be analyzed based on genetic replication in the Mexican Mestizo population. Zwingerman et al 26 showed that the Thr325Ile polymorphism demonstrated allele frequency variation by geographical region among European, Asian, and African populations, a finding that has also been reported in other studies. 27,28 When analysis was limited to cases of European origin, a significant difference was observed associated with the risk of venous thrombosis (OR = 0.83; P < .021).…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…Ethnic variation among TAFI haplotypes and SNPs should be analyzed based on genetic replication in the Mexican Mestizo population. Zwingerman et al 26 showed that the Thr325Ile polymorphism demonstrated allele frequency variation by geographical region among European, Asian, and African populations, a finding that has also been reported in other studies. 27,28 When analysis was limited to cases of European origin, a significant difference was observed associated with the risk of venous thrombosis (OR = 0.83; P < .021).…”
Section: Discussionsupporting
confidence: 69%
“…Sex subgroup analyses have found differences in SNP associations in CVT. In a meta-analysis, the minor allele of the rs3742264 SNP in a dominant model (AA+GA vs GG) was more frequent in female controls, and the Thr325Ile polymorphism was protective in Europeans independently of sex 26 ; despite this finding, 15% of SNPs have a sex-dependent susceptibility that could explain sexual dimorphism for thrombotic events. 33 In our sample, no differences in genotype, allele, or haplotype were observed between sexes in cases versus controls, which is similar the Ala147Thr and Thr325Ile SNPs and the risk of ischemic stroke in the Japanese population.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Subgroup analysis conducted based on ethnicity revealed similar results in different ethnic groups [ 117 ]. In accordance, the meta-analysis of Zwingerman and colleagues showed a decreased risk of VTE for the TT genotype versus the CT+CC genotype in both the overall and European study population, although not significant in the overall study population [ 118 ].…”
Section: Plasma Procpu Concentration and Procpu Polymorphisms As Rmentioning
confidence: 85%